Environnement BOKO HARAM et performance du secteur touristique : rupture ou continuité ? - Rosalie Christiane Nga Nkouma Tsanga (Études Caribéennes)
This research analyzes the relationship between insecurity and touristic activities by identifying the criteria for choosing a tourist destination and the reasons for choosing a risky destination and evaluating the effect of insecurity on the performance of the tourism sector. To do this, a triangular approach combining both a qualitative study and a double survey of 100 tourists and 87 actors of tourism sector seems relevant. The results of our study reveal, on the one hand, that the perception of risk, the attitude towards the destination of the Far North, the hedonist perceptions and the bias of optimism of the tourists are the factors determining the choice of this risky destination. On the other hand, they highlight the significant and negative impact of BOKO HARAM attacks on the performance of tourism sector activities in the region. The development of a compelling tourism branding and redesign of the marketing mix could help industry structures mitigate the negative effects of terrorism